Implementasi Program Desa Wisata Dalam Menunjang Pelestarian Dan Pengembangan Budaya Keris - Siti Ngaisah; Bagus Ananda Kurniawan; Chusnul Abadi (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2021)
ABSTRACT This study has objective to analyse the legal regulation as an effort to develop and maintain the art of Kris in Aeng Tong-tong Village, Saronggi, Sumenep. The methodology used is descriptive qualitative by using observation and interview as an analysis tools. The result of this study indicated that Kris as one of the heritages needed to be re-emphasize on its values and roles within society. Thus, there will be no more misunderstanding and misplacing the Kris. The conclusion of this study indicated that the implementation of tourism program which carried out by the Government was done to preserve the culture of Kris and make Sumenep as the city of Kris with huge amount of Kris maker in Indonesia. The implementation of the program was also supported by the legal regulation which regulated based on the order of law or hierarchy of statutory law. Keyword: Public Policy Implementation, Tourism Program, Tourism Regulation